Canine distemper outbreak and laryngeal paralysis in captive tigers (Panthera tigris) - Sarin Suwanpakdee; Anuwat Wiratsudakul; Nattarun Chaisilp; Luxsana Prasittichai; Anurux Skulpong; Patarapol Maneeorn; Benjaporn Bhusri; Chalisa Mongkolpan; Ruangrat Buddhirongawatr; Jarupa Taowan; Peerawat Wongluechai; Nlin Arya; et al. (BMC Veterinary Research)
Abstract The canine distemper virus (CDV) could infect various wildlife species worldwide. The viral infection in large felids directly impacts wildlife conservation. This study aimed to understand better the burden of CDV outbreaks in captive tiger populations in Thailand and a novel discovery of their clinical signs with a history of CDV exposure. We followed up on their infection from May 2016 to October 2020 with laboratory testing and veterinary medical records. The cumulative morbidity and mortality rates were relatively high. Moreover, 50% of the tigers survived at 2 years after infection. All suspected and confirmed cases of CDV infections were significantly associated with laryngeal inflammation, which developed into paralysis in almost 50% of cases. Altogether, 50% of all tiger cases with chronic infection developed stridor at 314 days after virus infection [95% CI: 302–320]. Therefore, laryngeal paralysis may result from CDV infection and degeneration, potentially affecting the peripheral and central nervous systems. This condition could pose a life-threatening risk to tigers. The virus could spread quickly by contact with bodily excretion among tigers and fomite contamination once it affects a specific population. Implementation of biosecurity measures and vaccination is essential to mitigate the risk of disease spread and infection rates in tiger populations.